Characterization of Methicillin-Resistant Staphylococcus Aureus Isolated from Cats and Dogs - Ng, Jacklyn Wei Sze (2006)
Globalization has entailed a massive increase in trade and human mobility facilitating the rapid spread of infectious agents, including those that are drug resistant.A particularly serious threat to human health is posed by methicillinresistant staphylococcal strains which have acquired molecular mechanisms to evade the β-lactam antibiotics (BLAs).The number of methicillin-resistant Staphylococcus aureus (MRSA) infection in humans is increasing,thus it seems likely that MRSA infection in animals is becoming more frequent too.This study addressed the significance of MRSA among cats and dogs, animal species that are in close proximity to humans. The first part of the study was designed to characterize the microbiological and biochemical properties of S.aureus and MRSA using both conventional and molecular methods. Samples comprising nasal and skin swabs collected from hospitalized and homeless cats and dogs at the University Veterinary Hospital, Universiti Putra Malaysia,(UVH-UPM) and animal shelter operated by the Society for the Prevention of Cruelty to Animals (SPCA) respectively between May to October 2004.The isolation and identification of MRSA using both the conventional and molecular methods in this study were found to be consistent and reliable. Conventional methods such as differential staining, biochemical tests,Slidex Staph Plus Kit (latex agglutination test) and selective media Mannitol Salt Agar (MSA) and Oxacillin Resistance Screening Agar Base (ORSAB) were used to detect the MRSA from cats and dogs.A total of seven (1.92%) MRSA out of 364 samples were successfully isolated from the animal subjects.These MRSA isolates were also found to be resistant to at least four antimicrobial agents.The second part of the study investigated the microbial resistance of the MRSA using molecular techniques.Polymerase Chain Reaction using specific primers amplified a 533-bp fragment of the mec A gene.The partial mec A gene sequences exhibited >97%amino acid similarities among the seven local MRSA isolates and the amino acid were highly conserved,and categorized in five different groups.Plasmid analysis indicated the presence of at least three plasmid bands in the seven MRSA isolates.In the last part of the study, the bacterial acid methyl esters (BAMEs) profile of the S.aureus and MRSA was characterized in order to detect probable differences between isolates and across host specificities.The branched chain 3-hydroxy dodecanoic, stearic and eicosaenoic acids were the principal fatty acids in both S.aureus and MRSA.However, lauric acid was unique to S. aureus only, whereas nonanoic acids were found more frequently among MRSA.Gradual changes in the fatty acid composition from S.aureus to animal MRSA and finally to human MRSA further reaffirmed the possibility of animal-human MRSA cross-transmissions.To our knowledge, this is the first report on the isolation of MRSA in animals and the use of molecular techniques to confirm the identity of the mec A gene from animals in Malaysia.The findings of the study would enable the formulation of suitable measures to control MRSA